2020
DOI: 10.18632/aging.103555
|View full text |Cite
|
Sign up to set email alerts
|

MiR-155 contributes to intestinal barrier dysfunction in DSS-induced mice colitis via targeting HIF-1α/TFF-3 axis

Abstract: Intestinal barrier dysfunction is a hallmark of inflammatory bowel disease (IBD). MiR-155 is increased in colitis and downregulates expression of hypoxia-inducible factor 1α (HIF-1α). Here, we investigated the effects of miR-155 on intestinal barrier dysfunction in dextran sulfate sodium (DSS)-induced colitis. We found that miR-155 antagomir treatment relieved weight loss and intestinal damage in IBD mouse models (P < 0.05). Furthermore, electron microscopy and immunofluorescence imaging showed that miR-155 in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 44 publications
(47 reference statements)
2
25
0
Order By: Relevance
“…However, mitochondria are not the only membranous organelles that alter shape and physiology upon colitis. Our previous study, in addition to reports by other authors, revealed the abnormal shape of multiple membranous organelles, including mitochondria, endoplasmic reticulum (ER) and Golgi apparatuses, and cellular and nuclear membranes during inflammation [ 37 , 38 , 39 , 45 , 46 , 47 ]. These indicate that membrane-forming phospholipids may be substantially deregulated upon colitis, which is further supported by experimental data [ 48 , 49 , 50 ].…”
Section: Introductionmentioning
confidence: 61%
“…However, mitochondria are not the only membranous organelles that alter shape and physiology upon colitis. Our previous study, in addition to reports by other authors, revealed the abnormal shape of multiple membranous organelles, including mitochondria, endoplasmic reticulum (ER) and Golgi apparatuses, and cellular and nuclear membranes during inflammation [ 37 , 38 , 39 , 45 , 46 , 47 ]. These indicate that membrane-forming phospholipids may be substantially deregulated upon colitis, which is further supported by experimental data [ 48 , 49 , 50 ].…”
Section: Introductionmentioning
confidence: 61%
“…MiR-155 promotes intestinal inflammation in UC and CD, probably via a variety of inflammation-related pathways [46,56,73,79,81,139]. In a recent study by Liu et al [144,145], it was shown that miR-155 mediates intestinal barrier dysfunction in DSS-induced mice colitis through targeting the HIF-1α/TFF-3 axis. Paraskevi et al [140] found that miR-155 is the most highly expressed UC-associated miRNA in blood samples, however, in the study by Schönauen [47], the authors did not find increased miR-155 levels in the blood from IBD patients, suggesting that more studies are needed to determine whether miR-155 is a putative blood-related biomarker.…”
Section: Mirnas and Cacmentioning
confidence: 99%
“…It increases IL-8 throughout the inflammatory process [ 78 , 79 ], modulates the inflammatory phenotype of intestinal fibroblasts and myofibroblasts via NF-κB [ 80 ]. A recent study showed that miR-155 mediates intestinal barrier dysfunction in DSS-induced mice colitis through HIF1α/TFF-3 axis [ 81 ]. The knock-down of miR-155 protects the experimental colitis mice by decreasing IFNγ, TNFα, IL-6, IL-12 and IL-17 production, reducing Th1 response and suppressing the T-cells activation by DCs [ 82 ].…”
Section: Micrornas Overexpression Induces Colitis-associated Colorectal Carcinogenesismentioning
confidence: 99%